2018
DOI: 10.1515/pteridines-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neopterin and its Significance as Biomarker in Differentiation of Mods From Sepsis

Abstract: Objective The aim of this study was to evaluate the dynamic changes of serum neopterin and its significance as biomarker in differentiation of MODS from sepsis. Methods Fifty eight critical illness patients and 21 healthy controls were included in the study. Of the included 58 critical illness patients, 37 cases were diagnosed of sepsis (sepsis group) and other 21 were non-sepsis subjects (non-sepsis group). Of the 37 sepsis patients, 17 were diagnosed of multiple organ dysfunction syndrome (MODS group). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…It is produced as the oxidation product of 7,8-dihydroneopterin, which is generated by IFN-γ (produced by T lymphocytes)-activated macrophages . Levels of neopterin can indicate infection, trauma, cancer, and cardiovascular disease and neopterin levels have been shown to be increased in sepsis patients, which is consistent with the findings in the current study. Some studies have shown that neopterin correlates with mortality in patients with sepsis and in one study in liver transplant patients, early post-transplant neopterin plasma levels were identified as a sensitive predictive marker of bacteremia and mortality 1 year post-transplant .…”
Section: Resultssupporting
confidence: 90%
“…It is produced as the oxidation product of 7,8-dihydroneopterin, which is generated by IFN-γ (produced by T lymphocytes)-activated macrophages . Levels of neopterin can indicate infection, trauma, cancer, and cardiovascular disease and neopterin levels have been shown to be increased in sepsis patients, which is consistent with the findings in the current study. Some studies have shown that neopterin correlates with mortality in patients with sepsis and in one study in liver transplant patients, early post-transplant neopterin plasma levels were identified as a sensitive predictive marker of bacteremia and mortality 1 year post-transplant .…”
Section: Resultssupporting
confidence: 90%
“…Ci et al found that the serum neopterin level of trauma patients and critical ill patients was higher than that of the healthy controls and serum neopterin level was positively correlated with the severity of the disease [24]. Studies have demonstrated that serum neopterin levels in patients with sepsis were elevated and can be used as a promising biomarker for multiple organ dysfunction syndrome (MODS) diagnosis in patients with sepsis [25][26][27]. In our work, the findings demonstrated that serum neopterin may reflect the severity of AP at a late stage and may be a potential serological maker for death prediction, which was in accordance with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al in his study showed that neopterin can help in differentiating MODS from sepsis. Along with above, we have calculated cut off for neopterin and also other markers and we have also compared the e cacy of different markers in sepsis and also in sepsis with MODS, which is novel in our study [13] and also the correlation of serum neopterin with the different sepsis scores was also calculated in our study.…”
Section: Mods and Nonmentioning
confidence: 91%